Capital Structure and Product Market Behavior: An Examination of Plant Exit and Investment Decisions - Kovenock, Dan; Phillips, Gordon M. (Review of Financial Studies, 1997)
We examine whether sharp debt increases through leveraged buyouts and recapitalizations interact with market structure to influence plant closing and investment decisions of recapitalizing firms and their rivals. We take into account the fact that recapitalizations and investment decisions are both endogenous and may be simultaneously influenced by the same exogenous events. Following their recapitalizations, firms in industries with high concentration are more likely to close plants and less likely to invest. Rival firms are less likely to close plants and more likely to invest when the market share of leveraged firms is higher.